EPC Agenda 2004-05-20 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda – Approved. Minutes of 2/27/2020 – Approved. Consent Items: From EPC: Curriculum Revisions: BA/BS Chemistry and BS Biochemistry; Early Childhood Studies BA, Early Childhood Studies Minor – Approved. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Associated Students Report. Statewide Senator Report. Staff Representative Report. From SAC: Statement on Cheating and Plagiarism – First Reading completed. From APARC: Recommendation to remove Appendix B from Program Review Policy – First Reading completed. APARC Report. EPC Report. SAC Report. CFA Report. Occasional Lecturers Report.